Diagnosis and Management of Interstitial Lung Abnormalities (ILA): An Article Review - Pande, I Wayan Pande Adhyaksa; Fachrucha, Fanny (Indonesian Society of Respirology (ISR), 2025)
Interstitial lung abnormalities (ILA) are radiological findings on chest computed tomography (CT) scans that occupy more than 5% of the lung area across upper, middle, and lower lung fields. Interstitial lung abnormalities manifest through several imaging features, including ground-glass opacities (GGO), reticular patterns, diffuse centrilobular nodules, non-emphysematous cysts, honeycombing, and traction bronchiectasis, while emphysema is excluded from its definition. Although global prevalence data for ILA are limited, epidemiological studies report a prevalence ranging from 3% to 10% in various populations. The ILA shares a similar pathological pathway with ILD. Histologically, the structural alterations are caused by a series of inflammations in the parenchyma, the part of the lung that is involved in gas exchange (bronchioles, alveolar ducts, and alveoli). Numerous proteins and pro-fibrotic components reside in this compartment. Connective tissue builds up because of these proteins' recurrent activation cycles. Identified risk factors for developing ILA include advanced age, cigarette smoking, exposure to inhaled substances such as dust and air pollution, and genetic predispositions. The ILA is further categorized into three subtypes: non-subpleural, nonfibrotic subpleural, and fibrotic subpleural, which reflect different radiological characteristics. Currently, there is no definitive treatment for ILA, and management strategies primarily involve clinical assessment, regular radiological follow-ups, and control of risk factors to mitigate disease progression. Given the potential implications of ILA on respiratory health, ongoing research is essential to elucidate its natural history and inform future therapeutic approaches.